Analisis Kepuasan Taruna/Taruni Terhadap Sekolah Tinggi Penerbangan Indonesia - Tiarto (Langit Biru: Jurnal Ilmiah Aviasi, 2017)
One of the efforts undertaken by managements STPI to improve quality in vocational education business competition is to improve the quality of service to customers in general and cadets in particular. The services provided include : the service of educators (lecturers / instructors), service personnel and various other public services that all require special handling in the implementation so that service users can feel the service as expected. Customer appraised service, performance and expectance assessment. Through statistical descriptive analysis of 22 service indicators, the value of customer satisfaction is 71.11% so that the value can be used as a reference to improve the quality of service in accordance with the expectations of service users